Тенденції розвитку галузі тваринництва в південному регіоні України - Болтянська, Лариса Олексіївна; Болтянская, Лариса Алексеевна; Boltianska, Larysa (ТДАТУ, 2020)
UK: В статті проведено аналіз сучасного стану галузі тваринництва в Україні та Південному регіоні, виявлені тенденції розвитку. За нинішніх умов в Україні існує значна кількість проблем повноцінного та ефективного функціонування ринку продукції тваринництва, зокрема необґрунтована державна політика, яка підкріпляється низькою прибутковістю виробництва продукції галузі та відповідно невисокою конкурентоспроможністю, ціновий диспаритет, недосконалість податкових, фінансових та бюджетних важелів, зниження умов життя сільського населення тощо. У продовж останніх років в господарствах усіх категорій країни та Південного регіону спостерігається скорочення поголів’я за всіма видами тварин. Динамічні процесів функціонування галузі, зокрема скорочення поголів’я тварин, мали неоднозначний вплив на показники валового виробництва продукції тваринницької галузі та продуктивності тваринництва. В цілому по країні спостерігається скорочення виробництва яловичини та телятини, молока і яєць. Досліджено, що темпи скорочення виробництва продукції тваринництва в сільськогосподарських підприємствах суттєво менші, ніж в господарствах населення. Тому, дана тенденція негативно відбивається на рівні споживання продукції тваринницької галузі населенням країни. RU: В статье проведен анализ современного состояния отрасли животноводства в Украине и Южном регионе, выявленные тенденции ее развития. В нынешних условиях на Украине существует значительное количество проблем полноценного и эффективного функционирования рынка продукции животноводства, в частности необоснованная государственная политика, которая подкрепляется низкой прибыльностью производства продукции отрасли и соответственно невысокой конкурентоспособностью, ценовой диспаритет, несовершенство налоговых, финансовых и бюджетных рычагов, снижения условий жизни сельского населения и тому подобное. В течении последних лет на предприятиях всех форм собственности страны и Южного региона наблюдается сокращение поголовья за всеми видами животных. Динамические процессы функционирования отрасли, в частности сокращение поголовья животных, имели неоднозначное влияние на показатели валового производства продукции животноводческой отрасли и продуктивности в животноводстве. В целом по стране наблюдается сокращение производства говядины и телятины, молока и яиц. Исследовано, что темпы сокращения производства продукции животноводства в сельскохозяйственных предприятиях существенно меньше, чем в хозяйствах населения. Поэтому, данная тенденция негативно отражается на уровне потребления продукции животноводческой отрасли населением страны. EN: In the article the analysis of the modern state of industry of stock-raising is conducted in Ukraine and South region, educed progress trends. At present terms there is a far of problems of the valuable and effective functioning of market of products of stockraising in Ukraine, a public policy that refreshes oneself subzero profitability of production of goods of industry and accordingly not high competitiveness is groundless in particular, price диспаритет, imperfection of tax, financial and budgetary leverages, decline of terms of life of rural population and others like that. In continue the last years in the economies of all categories of country and South region there is reduction of population after all types of animals. Dynamic processes of functioning of industry, in particular reduction of population of animals, had ambiguous influence on the indexes of gross production of goods of stock-raising industry and productivity of stock-raising. On the whole after a country there is a decline in the production of beef and veal, milk and eggs. Investigational, that the rates of decline in the production of goods of stock-raising in agricultural enterprises substantially less than, than in the economies of population. To Tom, this tendency is negatively reflected at the level of consumption of products of stock-raising industry by the population of country. Despite the declining livestock population in the country, there is an increase in the level of quality indicators of livestock production. During the analyzed period there is an increase in the average daily growth of cattle, pigs, increasing the average annual hopes for 1 cow. There is a steady trend towards the stability of the average weight of 1 poultry carcass. A similar trend in animal productivity is observed in farms in the Southern region. Judging by the research, it can be argued that the market of the livestock industry in Ukraine is promising, but this industry like no other needs government support.
Тенденции развития отрасли животноводства в южном регионе Украины
The progress of industry of stock-raising trends are in south region of Ukraine
Keywords: галузь тваринництва; чисельність поголів’я тварин; виробництво тваринницької продукції; продуктивність тварин; річне споживання; ринок продуктів тваринницького походження; отрасль животноводства; численность поголовья животных; производство животноводческой продукции; продуктивность животных; годовое потребление; рынок продуктов животноводческого происхождения; are industry of stock-raising; quantity of population of animals; production of stock-raising goods; productivity of animals; annual consumption; market of products of stock-raising origin